1995
DOI: 10.1177/004947559502500206
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Duodenal Ulcer and its Surgical Management in a Teaching Hospital in Bangladesh

Abstract: Duodenal ulcer patients with or without complications admitted in the surgical departments of Rajshahi Medical College Hospital (RMCH) during the period of 13 years from 1980-1992 were studied retrospectively. Duodenal ulcer accounted for 10/1000 admission and five operations per week. Of the 1623 patients with uncomplicated ulcer, only 623 needed surgical treatment. However, all of the 1599 who presented with pyloric stenosis, 1047 with peritonitis due to perforation, and 13 with hematemesis were operated upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…After screening the titles, 395 abstracts and 119 complete articles were reviewed, and 88 were selected for detailed evaluation. Of these, 59 were rejected for the reasons as follows: the study population was not a general population or the IRs were reported for NSAID users and non‐users, but no data were provided for estimating incidence among the general population ( n = 15); the outcome was UGIB, but the percentage of bleeding cases caused specifically by peptic ulcer was not provided ( n = 5); the same population was used by different studies ( n = 11), and only the most recent one is included; no IR estimates, person–time, or number of cases were available ( n = 13); the measure of frequency was prevalence rather than incidence ( n = 4); only mortality or operation rate was reported ( n = 9); and the outcome was DU or GU alone ( n = 1) . We excluded another study because it used a rough approximation of population at risk (denominator); moreover, it was the only eligible article from a non‐Western country .…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles, 395 abstracts and 119 complete articles were reviewed, and 88 were selected for detailed evaluation. Of these, 59 were rejected for the reasons as follows: the study population was not a general population or the IRs were reported for NSAID users and non‐users, but no data were provided for estimating incidence among the general population ( n = 15); the outcome was UGIB, but the percentage of bleeding cases caused specifically by peptic ulcer was not provided ( n = 5); the same population was used by different studies ( n = 11), and only the most recent one is included; no IR estimates, person–time, or number of cases were available ( n = 13); the measure of frequency was prevalence rather than incidence ( n = 4); only mortality or operation rate was reported ( n = 9); and the outcome was DU or GU alone ( n = 1) . We excluded another study because it used a rough approximation of population at risk (denominator); moreover, it was the only eligible article from a non‐Western country .…”
Section: Resultsmentioning
confidence: 99%
“…The advances in the medical treatment of the peptic ulcer disease have led to a dramatic decrease in the number of elective surgeries performed. However, the number of patients undergoing surgical intervention for complications such as perforation remains relatively unchanged or has increased [ 21 , 22 ]. Such patients present with the classical signs and symptoms of peritonitis, and need early surgery for a favourable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2 The elective operative management of peptic ulcer have drastically reduced but the cases that end up with perforations are still same or rather increased. 7 In present study, author noted these patients came with classical features of peritonitis and showed pneumoperitoneum on the X-ray. Immediate surgeries resulted in a favourable outcome.…”
Section: Duodenal Perforationsmentioning
confidence: 52%